Knockdown of LjALD1, AGD2‐like defense response protein 1, influences plant growth and nodulation in Lotus japonicus. Issue 11 (19th June 2014) - Chen, Wei; Li, Xueliu; Tian, Lu; Wu, Pingzhi; Li, Meiru; Jiang, Huawu; Chen, Yaping; Wu, Guojiang
Abstract The discovery of the enzyme L, L‐diaminopimelate aminotransferase (LL‐DAP‐AT, EC 2.6.1.83) uncovered a unique step in the L‐lysine biosynthesis pathway in plants. In Arabidopsis thaliana, LL‐DAP‐AT has been shown to play a key role in plant‐pathogen interactions by regulation of the salicylic acid (SA) signaling pathway. Here, a full‐length cDNA of LL‐DAP‐AT named as LjALD1 from Lotus japonicus (Regel) Larsen was isolated. The deduced amino acid sequence shares 67% identity with the Arabidopsis aminotransferase AGD2‐LIKE DEFENSE RESPONSE PROTEIN1 (AtALD1) and is predicted to contain the same key elements: a conserved aminotransferase domain and a pyridoxal‐5'‐phosphate cofactor binding site. Quantitative real‐time PCR analysis showed that LjALD1 was expressed in all L. japonicus tissues tested, being strongest in nodules. Expression was induced in roots that had been infected with the symbiotic rhizobium Mesorhizobium loti or treated with SA agonist benzo‐(1, 2, 3)‐thiadiazole‐7‐carbothioic acid. LjALD1 Knockdown exhibited a lower SA content, an increased number of infection threads and nodules, and a slight reduction in nodule size. In addition, compared with wild‐type, root growth was increased and shoot growth was suppressed in LjALD1 RNAi plant lines. These results indicate that LjALD1 may play important roles in plant development and nodulation via SA signaling in L. japonicus.